Indonesian Manufacturing Industry Performance towards Global Trade: An Analytical Review of Professionalism In Islam - Muslikhati Muslikhati; Rossanto Dwi Handoyo; Unggul Heriqbaldi (Universitas Muhammadiyah Malang, 2023)
Economic integration involves many countries was necessary to have superior products and competitiveness in the international market. Industrial performance was a benchmark for a country's export success. This study aims to estimate industrial performance by analyzing at the level of technical efficiency and Islamic views on work professionalism where this research analyzes the workforce used in the production process. The method used in this study is the stochastic frontier analysis (SFA) method. The results found that the level of technical efficiency of companies in the manufacturing industry in Indonesia between 2010 and 2015 with a total of 10,464 companies observed a trend of declining levels of company technical efficiency. In addition, labor as one of the inputs in production is not differentiated based on the level of education, skills and experience. The results imply that companies in the Manufacturing industry in Indonesia have internal problems related to the company's technical efficiency namely professionalism.